2011
DOI: 10.1128/cvi.05332-11
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Mannheimia haemolytica Recombinant Outer Membrane Proteins Serotype 1-Specific Antigen, OmpA, OmpP2, and OmpD15

Abstract: We previously identified Mannheimia haemolytica outer membrane proteins (OMPs) that may be important immunogens by using immunoproteomic analyses. Genes for serotype 1-specific antigen (SSA-1), OmpA, OmpP2, and OmpD15 were cloned and expressed, and recombinant proteins were purified. Objective 1 of this study was to demonstrate immunogenicity of the four recombinant OMPs in mice and cattle. Objective 2 was to determine if the addition of individual recombinant OMPs or combinations of them would modify immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
0
20
0
1
Order By: Relevance
“…These include the serotype 1-specific antigen, an uncharacterized outer membrane protein, as well as the outer membrane proteins P2 and OmpA. Especially OmpA and the serotype 1-specific antigen have previously been shown to be highly immunogenic in mice and cattle and are thus considered to be potential M. haemolytica vaccine candidates (Ayalew et al, 2011). Interestingly, OmpA from M. haemolytica and P. multocida share a sequence identity of 55%.…”
Section: Discussionmentioning
confidence: 99%
“…These include the serotype 1-specific antigen, an uncharacterized outer membrane protein, as well as the outer membrane proteins P2 and OmpA. Especially OmpA and the serotype 1-specific antigen have previously been shown to be highly immunogenic in mice and cattle and are thus considered to be potential M. haemolytica vaccine candidates (Ayalew et al, 2011). Interestingly, OmpA from M. haemolytica and P. multocida share a sequence identity of 55%.…”
Section: Discussionmentioning
confidence: 99%
“…An immunoproteomic study of M. haemolytica OMPs conducted in our laboratory identified 57 OMPs that may have the potential to be developed into vaccines (4). The immunogenicity of recombinant forms of several M. haemolytica OMPs, including PlpE, OmpA, PlpF, OmpP2, serotype 1-specific antigen (SSA-1), and OmpD15, has been studied (5)(6)(7)(8)(9)(10). Vaccination of calves with recombinant PlpE partially protects cattle against challenge with virulent M. haemolytica and significantly enhances the efficacy of commercial vaccines (7)(8)(9).…”
mentioning
confidence: 99%
“…Shewen and Wilkie (1988) demonstrated that immunity against M. haemolytica requires leukotoxin (LKT) neutralizing antibodies as well as antibodies against bacterial cell surface antigens. Studies in our and others' laboratories demonstrated that high antibody responses to OMPs, ranging from 16 to 86 kDa, correlated with resistance to challenge with virulent M. haemolytica S1, and vaccination of cattle with OMP-enriched cellular fractions from M. haemolytica S1 enhanced resistance of cattle against experimental challenge (Ayalew et al, 2010(Ayalew et al, , 2011aConfer et al, 2003Confer et al, , 2006Morton et al, 1995;Mosier et al, 1989;Orouji et al, 2012). In this regard, we used immunoproteomics, which uses a combination of 2D-gel electrophoresis (2-DE) and Western blotting with bovine convalescent sera, and identified 132 immunoreactive proteins in outer membrane preparations of M. haemolytica using LC-MS/MS.…”
Section: Introductionmentioning
confidence: 73%
“…M. haemolytica proteins whose immunogenicity have been established in ours and other laboratories include LKT (Gentry et al, 1985;Lo et al, 1987;Shewen and Wilkie, 1988), PlpE (Ayalew et al, 2004;Confer et al, 2003;Confer et al, 2006), PlpE-LKT chimera , serotype 1 specific antigen, OmpA, OmpD15, OmpP2 (Ayalew et al, 2011a,b), PlpF (Ayalew et al, 2011a, b), outer membrane vesicles (Ayalew et al, 2013), cholera toxin subunit B-PlpE-LKT chimera ), sialoglycoprotease (Shewen et al, 2003), GS60 (Lee et al, 2008;Orouji et al, 2012), adhesins (Kisiela and Czuprynski, 2009;Klima et al, 2014), and iron-regulated OMPs (Deneer and Potter, 1989;Potter et al, 1999). Representative M. haemolytica proteins whose immunogenicity has been shown in our earlier works and other investigators are given in Table 7.…”
Section: Secretomes As Multivalent Vaccinesmentioning
confidence: 93%